Divergent Synthesis of Five-Membered Nitrogen Heterocycles via Cascade Reactions of 4-Arylfuroxans - Chaplygin, Daniil A.; Ananyev, Ivan V.; Fershtat, Leonid L.; Makhova, Nina N. (Synthesis, 2020)
A novel method for the synthesis of a diverse series of functionally substituted five-membered heterocyclic compounds via atom-economic, regio-, and diastereoselective one-pot reaction cascade was developed. This approach involves a ring opening in 4-arylfuroxans to α-oximinoarylacetonitrile oxides followed by [3+2] cycloaddition to various dipolarophiles to afford multisubstituted isoxazoles and isoxazolines. Subsequent azole–azole rearrangement of (oximino)isoxazolines/-isoxazoles, which can be conducted in a one-pot manner, results into functionally substituted furazans formation. The developed protocol is operationally simple, proceeds in mild conditions and with high yields of target heterocyclic systems. Overall, this study represents a new mode of isoxazole and 1,2,5-oxadiazole functionalization strategy, which is useful in medicinal and materials chemistry.
Keywords: nitrogen heterocycles; 1,2,5-oxadiazole; rearrangement; cascade reactions; [3+2] cycloaddition